1990
DOI: 10.1103/physrevlett.65.1164
|View full text |Cite
|
Sign up to set email alerts
|

Defect independence of the irreversibility line in proton-irradiated Y-Ba-Cu-O crystals

Abstract: Flux pinning in Y-Ba-Cu-O crystals is studied as a function of fluence of 3-MeV protons, which create random local defects. Order-of-magnitude increases in the critical current density are deduced from magnetic hysteresis loops, with values up to 2x 10 5 A/cm 2 observed at 77 K and 1 T. However, the irreversibility line in the field-temperature plane and the pinning potentials deduced from flux-creep studies are hardly changed. These results are compared to melting and pinning models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
162
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 474 publications
(177 citation statements)
references
References 23 publications
15
162
0
Order By: Relevance
“…The relaxation rate is in accordance with the usually reported value of 0.03 for single-crystal and ceramic YBCO samples. 1,14 With respect to t 0 , the results are in agreement with the extrapolated values in temperature from Ref. 15.…”
Section: B Magnetic Relaxationsupporting
confidence: 79%
“…The relaxation rate is in accordance with the usually reported value of 0.03 for single-crystal and ceramic YBCO samples. 1,14 With respect to t 0 , the results are in agreement with the extrapolated values in temperature from Ref. 15.…”
Section: B Magnetic Relaxationsupporting
confidence: 79%
“…These fluctuations enable vortex depinning via different types of excitations, thus effectively reducing J c . 49 In Figure 5d, we find that S is significantly reduced with respect to that of (Y,Gd)BCO when NPs are included. The stronger the pinning, the smaller S is; however, more importantly, the reduction of S(H) continues up to higher field strengths with an increasing density of BMO NPs; the maximum field for the low creep onset (μ 0 H(S onset )) is 1.5 T for the +12BZO (d coat = 150 nm) film and 3.5 T for the +12BHO (d coat = 30 nm) film (see arrows in Figure 5b).…”
Section: Dramatically Higher J C With Nearly Isotropic Angular Dependmentioning
confidence: 66%
“…Several models have been proposed to explain J c (T, H, θ) in cuprate and pnictide superconductors with strong pinning NPs or NRs. 21,24,[50][51][52][53][54][55][56][57][58][59] Although the influence of creep Tuning NP size for enhanced functionality M Miura et al on J c for these superconductors has been known for a long time, 49,60 only a few attempts have been made to link the pinning improvements to J c and S. 60,61 To calculate the temperature, magnetic field and field angle dependence of J c (J c;calc: ), we use J c;calc: T; H; y ð Þ¼ J c0 T; H; y ð Þ1 À Sln t=t 0 ð Þ ð Þ , where t 0 is the effective attempt time, J c0 is the creep-free J c and S is the experimentally obtained flux creep rate.…”
Section: Dramatically Higher J C With Nearly Isotropic Angular Dependmentioning
confidence: 99%
“…15 It is also important that artificial microscopic defects or inclusions in superconductors are effective in increasing critical current densities. Introduction of defects by irradiation in YBa 2 Cu 3 O 7 has been proved [16][17][18][19] to result in sharp increases of critical temperatures and fields in the irreversible region. Using the top-seed-melt-textured growth process, Murakami et al 20 doped Y 2 BaCuO 5 (Y211) inclusions into the YBa 2 Cu 3 O 7−x (Y123) matrix and found that the flux-pinning force can be improved due to the dispersion of nonsuperconducting Y211 inclusions.…”
Section: Introductionmentioning
confidence: 99%